Understanding Extreme Sports: A Psychological Perspective - Brymer, Eric; Feletti, Francesco; Monasterio, Erik; Schweitzer, Robert D. (Frontiers Media SA, 2020)
Extreme sports, those activities that lie on the outermost edges of independent adventurous leisure activities, where a mismanaged mistake or accident would most likely result in death, have developed into a significant worldwide phenomenon (Brymer& Schweitzer, 2017a). Extreme sport activities are continually evolving, typical examples include BASE (an acronym for Buildings, Antennae, Span, Earth) jumping and related activities such as proximity flying, extreme skiing, big wave surfing, waterfall kayaking, rope free solo climbing and high-level mountaineering. While participant numbers in many traditional team and individual sports such as golf, basketball and racket sports have declined over the last decade or so, participant numbers in so called extreme sports have surged. Although extreme sports are still assumed to be a Western pastime, there has been considerable Global uptake. Equally, the idea that adventure sports are only for the young is also changing as participation rates across the generations are growing. For example, baby boomers are enthusiastic participants of adventure sports more generally (Brymer & Schweitzer, 2017b; Patterson, 2002) and Generation Z turn to extreme sports because hey are popular and linked to escapism (Giannoulakis & Pursglove, 2017) . Arguably, extreme sports now support a multi-billion dollar industry and the momentum seems to be intensifying. Traditional explanations for why extreme sports have become so popular are varied. For some, the popularity is explained as the desire to rebel against a society that is becoming too risk averse, for others it is about the spectacle and the merchandise that is associated with organised activities and athletes. For others it is just that there are a lot of people attracted by risk and danger or just want to show off. For others still it is about the desire to belong to sub-cultures and the glamour that goes with extreme sports. Some seek mastery in their chosen activity and in situations of significant challenges. This confusion is unfortunate as despite their popularity there is still a negative perception about extreme sports participation. There is a pressing need for clarity. The dominant research perspective has focused on positivist theory-driven perspectives that attempt to match extreme sports against predetermined characteristics. For the most part empirical research has conformed to predetermined societal perspectives. Other ways of knowing might reveal more nuanced perspectives of the human dimension of extreme sport participation. This special edition brings together cutting-edge research and thought examining psychology and extreme sports, with particular attention payed to the examination of motivations for initial participation, continue participation, effective performance, and outcomes from participation.